EFFECTS OF ORAL FLUIDS AND INTRAVENOUS FLUIDS IN THE IMPROVEMENT OF AMNIOTIC FLUID INDEX DURING THIRD TRIMESTER OF PREGNANCY - Mehwish Malik (Army Medical College Rawalpindi, 2021)
Objective: To assess the effects of oral fluids and intravenous fluids in terms of frequency of improving Amniotic Fluid Index during third trimester of pregnancy having oligohydramnios. Study Design: Comparative prospective survey.